The crustal assimilation in alkaline basic magmas: the Ponte Nova mafic-ultramafic massif and dikes/plugs of the Mantiqueira Range (SP-MG), Brazil - Ambrosio, Mariana Robertti (2022)
This study aimed to investigate the impact of crustal assimilation on the SiO2- undersaturated Cretaceous alkaline rocks emplaced in the Mantiqueira mountain range in the northern sector of the Serra do Mar alkaline Province, southeastern Brazil. The focus was the most contaminated intrusions of the Ponte Nova alkaline massif, PNAM, the cumulate western intrusion (WI) and the porphyritic southern satellite intrusion (SSA), as well as the nearby basic/intermediate dikes and plugs. The study of disequilibrium textures, mineral chemistry and Sr isotope ratio in plagioclase and alkali feldspar crystals were employed to infer the processes occurred in different stages of magma evolution of PNAM in shallow crustal depths. The mineral isotope analyses were carried out using polytetrafluoroethylene filter and holder device to combine Laser Ablation (LA) as the sampling technique with Thermal Ionization Mass Spectrometry (TIMS). The chemical patterns observed in crystals were interpreted as the effect of AFC in the main stage of the evolution and the competition between AFC and magma recharge in the following stage. The sharp transition between core and rim of feldspar crystals and the disequilibrium textures of the respective cores reinforce mainly the abrupt chemical change of the system during their crystallization. SSA (represented by nepheline-bearing monzogabbros and nephelinebearing melamonzonites) may represent a magma recharge that came after the SSA-nph-mz (nepheline-bearing monzonites) emplacement, however the intrusion did not achieve the complete homogeneity as the petrographic and chemical data indicate. Assimilation of partial melt of crustal xenoliths and from the wall rock were pointed out as two mechanisms responsible for the PNAM contamination in agreement with previous studies. According to the results of modeling by Magma Chamber Simulator (MCS), the presence of Ba-rich minerals in the PNAM, especially Ba-rich feldspars, may be resultant of extensive fractional crystallization of enriched primitive melts and increase of SiO2 activity by crustal assimilation. The patterns of Ba and Sr composition observed in plagioclase corresponds to those simulated using logDBa or Sr pl/melt as a function of 1/T rather than constant coefficient values. The degree of scattering of trace element data in the analyzed crystals may be related to the disequilibrium crystallization and chemical heterogeneities in the magma chamber. The studied basic/intermediate dikes and plugs varies from phonotephrite to tephriphonolite or trachyandesite to trachyte. The interaction of them with the acid wall rock in shallow depth of the crust is observed by their sinuous contacts and the presence of rounded crustal xenolith hosted in the alkaline rocks. The dikes and plugs are emplaced mainly in Precambrian batholith of Serra da Água Limpa and subordinately in the PNAM or in the medium-grained hololeucogranite which age (579.5 Ma) was obtained with U-Pb dating of zircon crystals. The occurrence of (open or closed) monomineralic or polymineralic glomerocrysts in dikes and plugs suggests that magmas were stored in a magma chamber environment before ascending. Major- and trace-element contents of whole rock show that the magmas passed by extensive fractional crystallization of mafic minerals before reaching the shallower depth of the crust. The data fall in the field limited by magma mixing curves (basanite x silicic melts) constructed with ratios of highly incompatible elements (e.g., Nb/Pb, Th/Pb x Rb/Sr) or isotopes ((87Sr/86Sr)i x (143Nd/144Nd)i). AFC modeled by thermodynamic software (MCS) starting with a basanite magma supports that the crustal contamination has taken place mainly in upper crust (granitoid) where the partial melting could be greater under specific circumstances (e.g., earlier crustal heating, steep geotherm) rather than in lower crust (granulite). Likewise, part of data for major element oxides lies on the field formed with AFC and FC/magma mixing curves obtained by MCS. On other hand, AFC curves constructed using trace-element ratios (e.g., Nb/Pb, Th/Pb) do not reach most sample data likely due to the effect of mineral crystallization on the ratios used and the model uncertainties added in the selection of starting composition of the subsystems (main magma and wall rock) and trace-element partition coefficients. This study proposes that the crustal assimilation of dikes and plugs may have occurred during the magma ascent and possibly in a magma chamber in the upper crust. Among the factors that may have caused the lower level of crustal contamination of dikes and plugs compared to that found in WI and SSA/SSA-mz, it is cited the laminar regime of magma flow, the presence of chilled margin and the lower time of contact between magma and wall rock.